2012
DOI: 10.1161/circulationaha.112.099937
|View full text |Cite
|
Sign up to set email alerts
|

C1q/Tumor Necrosis Factor-Related Protein-3, a Newly Identified Adipokine, Is a Novel Antiapoptotic, Proangiogenic, and Cardioprotective Molecule in the Ischemic Mouse Heart

Abstract: Background Obesity/diabetes adversely affects post-ischemic heart remodeling via incompletely understood underlying mechanisms. C1q/TNF-related protein-3 (CTRP3) is a newly identified adipokine exerting beneficial metabolic regulation, similar to adiponectin. The current study determined whether CTRP3 may regulate post-ischemic cardiac remodeling and cardiac dysfunction, and, if so, sought to elucidate the involved underlying mechanisms. Methods and Results Male adult mice were subjected to myocardial infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
153
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 30 publications
13
153
0
6
Order By: Relevance
“…41 C1q and tumor necrosis factorrelated protein 9 secreted by fat cells is also cardioprotective, proangiogenic, and antiapoptotic, 42 and increased C1q and tumor necrosis factor-related protein 9 could restore cardiac function, attenuate cardiomyocyte apoptosis, and increase neovascularization in hypoxia-induced cardiomyocyte injury. 43 Therefore, it is likely that intramyocardial adipocytes in the normal heart exert a protective role for cardiomyocytes and coronary vessels through paracrine mechanism, which merits further investigation in the future. However, excessive adipocytes might also be associated with cardiovascular diseases, such as arrhythmogenic right ventricular cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…41 C1q and tumor necrosis factorrelated protein 9 secreted by fat cells is also cardioprotective, proangiogenic, and antiapoptotic, 42 and increased C1q and tumor necrosis factor-related protein 9 could restore cardiac function, attenuate cardiomyocyte apoptosis, and increase neovascularization in hypoxia-induced cardiomyocyte injury. 43 Therefore, it is likely that intramyocardial adipocytes in the normal heart exert a protective role for cardiomyocytes and coronary vessels through paracrine mechanism, which merits further investigation in the future. However, excessive adipocytes might also be associated with cardiovascular diseases, such as arrhythmogenic right ventricular cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that an absence of overt metabolic phenotypes seen in the Ctrp3-KO mice does not, in principle, negate its potential beneficial metabolic properties when recombinant protein is administered in vivo, as illustrated by its ability to markedly reduce hepatic triglyceride levels in obese WT mice with existing liver steatosis (40). Elevating plasma levels of CTRP3 can also have beneficial cardiac effects in conditions of ischemic heart attack (69). There are obvious limitations in our current study in which we employ a whole body KO mouse model deficient in CTRP3 protein throughout development and in adult animals.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond metabolic control, recent studies have also shown that CTRP3 has anti-inflammatory properties (22,23,48) as well as cardioprotective effects in mouse models of ischemic heart attack (69). Interestingly, overexpressing CTRP3 in mice also promotes phosphate-induced vascular smooth muscle cell calcification (73).…”
mentioning
confidence: 99%
“…CTRP3 replenishment improves survival and restores cardiac function after MI and attenuates post-ischemic pathologic remodeling (evidenced by echocardiographic and histologic parameters). 93 Preventing post-MI CTRP3 inhibition or CTRP3 supplementation may aid in the restoration of cardiac function and mitigate heart failure sequelae ( Figure 5). …”
Section: Ctrp3mentioning
confidence: 99%